Domestic Violence and Child Mortality - Samantha Rawlings; Zahra Siddique (Institute of Labor Economics (IZA), 2018)
We examine the effect of domestic violence on mortality of children born to female victims using Demographic and Health Survey (DHS) data across thirty two different developing countries. We start by examining associations between interpersonal violence and child mortality while controlling for potential confounds. We find that children of (ever) victimized mothers are 0.4 pp more likely to die within thirty days, 0.7 pp more likely to die within a year and 1.1 pp more likely to die within the first five years of being born in comparison with children born to mothers who never experienced violence. We find similar patterns when examining the effect of violence taking place in the last twelve months on female victims and their children. Our results are similar when we use matching methods. We also examine the causal effect of violence on child mortality using an instrumental variables strategy. Exploiting variation in domestic violence and marital rape laws across countries and over time, we find that laws that criminalize violence against women and/or marital rape lower its incidence. Using this as an exogenous source of variation in domestic violence, we find that children born within the last twelve months to female victims were 3.7 pp more likely to die in the first thirty days of life. Our results indicate significant externalities to violence against women and underline the importance of recent efforts to tackle this violence in developing countries.
Keywords: I14; J12; J13; 330; child mortality; domestic violence